FAKTOR-FAKTOR YANG MEMPENGARUHI NIAT UNTUK MELAKUKAN WHISTLEBLOWING INTERNAL (The Factors Influencing Internal Whistleblowing Intentions) - Intan Setyawati; Komala Ardiyani; Catur Ragil Sutrisno (Fakultas Ekonomi Universitas Pekalongan, 2016)
The purpose of this research is to examine the influence of ethical climate, organizationalcommitment, personal cost, and seriousness of wrongdoing on whistleblowing intentions. It usespurposive sampling method to employees of National Public Procurement Agency of Indonesia (NPPA).The results of multiple regression analysis show that ethical climate principle and seriousness ofwrongdoing have significant effect on internal whistleblowing intentions whereas ethical climateegoism, ethical climate benevolence, organizational commitment and personal cost do not havesignificant effect on internal whistleblowing intentions.Keywords: internal whistleblowing, ethical climate, organizational commitment, personal cost,seriousness of wrongdoing.